Constructive engagement for the civil society and the private sector, especially for resource mobilization - Abraham, Martin (Malaysian Journal of Science, 2010)
With the onset of the global financial recession, the decline in the transfer of Overseas Development Assistance (ODA) from the industrialized nations, the slow down in the investments from foreign donors and investors, etc, the challenges of resource mobilization, particularly in the sourcing and securing of funds for the implementation of sustainable development projects and programmes, is becoming increasingly difficult and cumbersome, especially for the range of not-for-profit Non-Governmental Organizations (NGOs), Community-Based Organizations (CBOs), Indigenous Peoples Organizations (IPOs), Civil Society Organizations (CSOs), etc, that are located in or working in developing countries. Under the prevailing circumstances, the roles of the profit-oriented private sector corporations are becoming much more significant and critical in their serving as alternate or co-financing sources of funding for such organizations, especially under the aegis of their individual or collective Corporate Social Responsibilities (CSR). However, based on a number of past experiences and proven episodes, it would be wise for the organizations concerned to adopt and to integrate appropriate checks, balances and indicators, to ensure that the resource mobilization relationships seeded and nurtured between the public-interest or civil-society groups and the private sector institutions are, indeed for the purposes of satisfying their intended dictums of "constructive engagements".